2012
DOI: 10.1016/j.virusres.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pepino mosaic virus capsid protein interacts with a tomato heat shock protein cognate 70

Abstract: Plant viral capsid proteins (CP) can be involved in virus movement, replication and symptom development as a result of their interaction with host factors. The identification of such interactions may thus provide information about viral pathogenesis. In this study, Pepino mosaic virus (PepMV) CP was used as bait to screen a tomato (Solanum lycopersicum) cDNA library for potential interactors in yeast. Of seven independent interacting clones, six were predicted to encode the C-termini of the heat shock cognate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 88 publications
0
43
0
Order By: Relevance
“…It is also possible that heat-shocked plants support greater cell-to-cell movement of CNV, as has been reported previously for other viruses (9,22,37). In addition, heatshocked plants might display compromised resistance to CNV, allowing for increased spread.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…It is also possible that heat-shocked plants support greater cell-to-cell movement of CNV, as has been reported previously for other viruses (9,22,37). In addition, heatshocked plants might display compromised resistance to CNV, allowing for increased spread.…”
Section: Resultsmentioning
confidence: 62%
“…Hsp70 is activated under stress conditions such as heat, virus infection, and oxidative stress (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Whereas Hsc70 is generally expressed constitutively, it can also be induced by environmental stresses such as thermal and pesticide stress, as well as virus infection (10,(20)(21)(22)(23). It has also been found that Hsp70 and Hsc70 may complement each other in a synergistic manner to preserve cellular integrity during metabolic challenges (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to protecting viral genomes by forming protective capsids, they can affect viral pathogenesis through its implication in almost all stages of the viral life cycle, beginning with processes that enhance virus entry into plant cells to those that facilitate the transmission of viruses from plant to plant. For example, PepMV CP has been shown to interact with a tomato heat shock protein and thereby influence viral symptoms (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports, particularly on positive-strand RNA viruses of plants, examined the key role of cellular chaperones and folding enzymes. During plant virus infection, several Hsp proteins are involved in the formation of membrane-bound RCs for certain members of the Tombusvirus, Tobamovirus, Potyvirus, and Potexvirus genera (50)(51)(52)(53). There are several cochaperones, including Hsp40, that associate with the bromovirus RC (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%